PENGARUH CASH RATIO, DEBT TO ASSET RATIO DAN TOTAL ASSET TURNOVER TERHADAP NET PROFIT MARGIN PADA PT PROFESIONAL TELEKOMUNIKASI INDONESIA TBK. PERIODE 2013 – 2023 - Firdiana, Fazira; Nugroho, Riski Dwi (Journal of Research and Publication Innovation, 2024)
This research aims to find out how the impact of Cash Ratio (CR), Debt to Asset ratio (DAR) and Total Asset Turnover (TATO) on Net Profit Margin (NPM) at PT Profesional Telekomunikasi Indonesia Tbk. both partially and simultaneously. The type of research carried out is descriptive quantitative using the type of secondary data obtained from the Financial Report of the Publication of PT Profesional Telekomunikasi Indonesia Tbk. from the official website of PT Profesional Telekomunikasi Indonesia Tbk. from 2013 until 2023. The data analysis methods used include Classical Assumption Testing, which includes Normality Test, Multokolinierity Test, Heterokedastisity Test and Autocorrelation Test. Additionally, Simple and Multiple Linear Regression Analysis, Correlation Coefficient Test, Determination coefficients Test, Hypothesis Test (T Test), and Simultaneous Test (F Test) with X1 Cash Ratio variable (CR), X2 Debt to Asset Ratio (DAR), X3 Total Asset Turnover (TATO) variable, and Y Variable Net Profit Margin (NPM). CR test results have no effect on NPM with T test partially with tcount < ttable is 0,380 < 2,3646 and significant value is 0,715 > 0,05. DAR significantly negatively influenced on NMP with tcount > ttable is 3,679 > 2,3646, and significant value is 0,008<0,05. TATO significantly negative influence on NPM with tcount > ttable is 2,829 > 2, 3646 and significant value is 0,025 < 0,055. CR, DAR, and TATO against NPM with known F test, Fcount is greater than Ftable is 5,873 > 4,35 and signifying value is 0.025 < 0.05. So the explanation that the variable that CR, DAR, TATO proved positive and significantly influence simultaneously on NPM with significant values is 0,025.